Weekly Procalcitonin Kinetics as an Early Biomarker of Treatment Response in Stage III Non-Small Cell Lung Cancer Undergoing Concurrent Chemoradiotherapy: A Multicenter Prospective Observational Study - Sohaib, Ahmed; Genena, Shaimaa E.R.; Abdelhafiz, Nora; Alhefny, Mohamed; Elabd, Naglaa; Hebesh, Eman H (Asian Pacific Journal of Cancer Care, 2025)
Background: Early identification of response during concurrent chemoradiotherapy (cCRT) for stage III non-small cell lung cancer (NSCLC) could critically inform clinical decision-making, particularly regarding surgical candidacy, modification or completion of therapy, and optimal integration with immunotherapies. This prospective study evaluates weekly serum procalcitonin (PCT) kinetics as a biomarker of treatment response in stage III NSCLC receiving cCRT, analyzing the potential to guide individualized care pathways. Methods: In this multicenter prospective observational study, adults aged 18–65 years with stage III NSCLC eligible for upfront concurrent chemoradiotherapy (cCRT) were enrolled. Key exclusions were elevated baseline procalcitonin (PCT > 0.1 ng/mL), active infection at baseline or during cCRT, autoimmune disease, incomplete radiotherapy, or ECOG 3–4. Serum PCT was measured at baseline and weekly during radiotherapy. Tumor response was assessed 4–6 weeks post‑cCRT by RECIST v1.1. PCT trajectories were analyzed using mixed‑design repeated‑measures ANOVA (Time × Response), with non‑parametric alternatives as needed. Logistic regression evaluated baseline and early PCT changes as predictors of response, and ROC analysis determined AUC, sensitivity, specificity, and optimal cut‑offs. Analyses were performed in SPSS v20; p < 0.05 was considered significant. Results: Of 79 screened, 73 were evaluable (5 CR, 24 PR, 27 SD, 17 PD). Responders (n=29) exhibited a consistent transient PCT peak at week 2 or 3, followed by a progressive decline. Non-responders (n=44) lacked this pattern, showing rather stable or irregular pattern of PCT levels. Repeated measures LMEM demonstrated a significant time × response effect (p<0.001). Logistic regression incorporating early PCT rise predicted response (AUC=0.84). Integration of PCT kinetics could support decisions to proceed to surgery or continue radiotherapy without interruption, obviating delays for radiologic confirmation. Conclusions: This is the first prospective report of PCT kinetics as a biomarker of cCRT response in lung cancer. A characteristic early, transient PCT rise followed by decline is associated with treatment response. Dynamic PCT monitoring can enable real‑time, individualized decision‑making, including timing for surgical evaluation and potential for mid‑treatment immunotherapeutic intensification.